THE ROLE OF MEDIA IN PROMOTING DIGITAL CULTURE AMONG YOUNG PEOPLE CHALLENGES AND SOLUTION - Zainalabdain Ali Jeryo; Dr. Ahmed Jaber Khayoon (American Journals Publishing, 2025)
This research aims to study the role of media in promoting digital culture among young people, focusing on the challenges faced by this role and possible solutions to overcome them. In light of the accelerating technological transformations, the media has become an essential part of the daily life of young people, as it represents a key means of learning and interacting with the digital world. With the increasing use of digital media by young people, there is an increasing need to strengthen their digital culture, which includes the ability to handle modern technologies safely and effectively, as well as developing critical thinking skills and conscious interaction with digital content.The research deals with the role of traditional and digital media in promoting digital culture, while studying the challenges faced in this area such as the spread of misinformation, the growing digital gaps, and the negative effects on the mental health of young people. The research also aims to provide possible solutions to overcome these challenges, including developing awareness-raising media content, enhancing cooperation between educational and media institutions, and motivating young people to use technologies more consciously.To achieve the research goals, a descriptive-analytical approach was used, in which data were collected through questionnaires and interviews with young people, experts in media and technology, as well as analysis of media content aimed at young people. The research found that media can be an effective tool in promoting digital culture, but digital media strategies need to be improved and provide meaningful content that enhances digital skills and meets current challenges.In the end, the study seeks to provide practical recommendations aimed at improving the role of media in promoting digital culture, which contributes to enabling young people to deal with the digital age safely and responsibly.
Keywords: Youth awareness, Providing educational content, Youth orientation, Encouraging positive use, Building risk awareness, Enhance critical thinking skills, Challenges, solutions.